Classification of Malaysian Soil Species Based on FTIR and Laser Raman Spectroscopy Analysis - Mohd Kahar, Nurul Nadzirah; Embong, Zaidi (Enhanced Knowledge in Sciences and Technology, 2022)
This study focused on the characterization of soil species by using Fourier Transform Infrared (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy with energy-dispersive X-ray (SEM-EDX) and Raman Spectroscopy. The objectives of this study are to measure the elemental composition in several morphology of soil in Johor state using SEM-EDX and XRD, to characterize the functional group and molecular structure for each soil species using FTIR and Laser Raman Spectroscopy and to compile the information of elemental composition, functional group, and molecular structure for Malaysian soil species database. There are five types of soil species studies which are Selangor- Kang Kong, Rengam- Jerangau, Keranji, Kulai- Yong Peng and Peat were obtained from soil in Pasir Gudang and Batu Pahat, Johor. This analysis was to measure the elemental composition, molecular structure and their functional group in the soil species. The sample preparation began with the collection of soil and then dried all five soil samples in the oven for 24 hours. The soil samples that have been dried will be grinding with postal and mortar until the soil turns into powder. The powder for all soil species will be divided into four different instruments. The soil species were analyzed in the Fourier Transform Infrared (FTIR) to examine the functional group. The most functional group that can be found in the soil is H-bonded and O-H stretch. Next, the soil samples were also analyzed in X-ray Diffraction (XRD) to investigate the soil particle and crystallographic structure. Peak in XRD graphs were used to find the nature of the material, the sharp peak of the material will be known as crystalline while the broader peak will be categorised as amorphous and the combination of both peaks is semicrystalline. Other than that, Scanning Electron Microscopy with energy-dispersive X-ray (SEM-EDX) analyzed the soil samples to study the morphology and elemental composition. The most common elements that can be found in the soil were oxygen (O), carbon (C), potassium (K), aluminum (Al) and silicon (Si). The last instrument was Raman Spectroscopy to scan the molecular structure.